THE POTENTIAL OF TRIGONA CULTIVATION IN IMPROVING THE ECONOMY OF THE MUARO BATUAK JAYA FOREST FARMERS GROUP COMMUNITY - Luthfiani, Puti; Milantara, Noril; Lensari, Delfy (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
cultivated products, except wood originating from forests. One example is the cultivation of Trigona Itama honey bees (Heterotrigona itama). Trigona honey bees have long been cultivated by the community, both for personal consumption and as a product that can improve the community's economy. The Muaro Batuak Jaya Forest Farmers Group (KTH) was founded on March 1 2021, with the chairmanship of Mr. Megi Wijaya with 18 members and 15 active members. KTH Muaro Batuak Jaya has potential in Galo-galo Trigona itama Honey. This research aims to analyze the potential of Trigona cultivation in improving the economy of the KTH Muaro Batuak Jaya community. This research uses interview and observation methods. The galo-galo bee (Trigona Sp) is a stingless bee which is one of the NTFPs which is rich in benefits and has a high market value. The process of cultivating Galo-Galo Trigona Itama (Heterotrigona itama) Honey is carried out in various stages starting from harvesting techniques to processing by selecting good colonies, making stup using durable wood. Maintenance involves maintaining cleanliness and checking the colony once every 2 weeks, selecting the cultivation location by keeping it away from ants and smoke and close to honey-producing plants, and harvesting is done by vacuuming, the first harvest takes 6 months. After harvesting, the honey that is ready to be harvested is filtered first to be put into packaging and ready to be marketed. At KTH Muaro Batuak Jaya, 250 ml packaging is available with a selling price of IDR 100,000,- from 80 setups giving a turnover of IDR. 8,000,000,- per month.